Standardization of gamma irradiation doses for microbial decontamination and quality preservation in walnut kernels grown in temperate climate of western himalayas - Yaseen, Mifftha; Jabeen, Abida; Hussain, Syed Zameer; Gautam, Satyendra; Nazir, Nageena; Bashir, Shubli; Kousar, Mumtahin-Ul (Frontiers in Food Science and Technology, 2025)
IntroductionIndia is among major walnut producer, but post-harvest losses due to fungal infections, aflatoxin contamination, and poor storage affects both domestic consumption and export potential. Therefore, effective solutions like irradiation technology are needed to improve quality and marketability. This study evaluates the efficacy of gamma irradiation (0, 1, 2, 3, 4, and 5 kGy) on the quality and safety of Indian walnuts at two moisture levels, including 5% and 8%.MethodsSamples were exposed to Cobalt-60 source, and the irradiated products were studied in terms of the physicochemical parameters, fatty acid profile, aflatoxin content, color, texture, and sensory attributes.Results and DiscussionIrradiation at 3 kGy (for 5% moisture) and 2 kGy (for 8% moisture) emerged as standardized doses, significantly reducing peroxide value (by up to 64%) and free fatty acids (by up to 45%) compared to non-irradiated control samples. Concurrently, total aflatoxin concentrations (B1, B2, G1, G2) dropped to near-minimal levels-up to 80% – 90% reduction relative to controls, ensuring compliance with international aflatoxin standards [(European commission (NMT 4 ppb) and US (NMT 20 ppb), Netherlands (0 ppb) and Switzerland (1 ppb)]. Fatty acid profiling revealed minimal degradation in essential PUFAs such as linoleic and alpha-linolenic acids (p < 0.05 at standardized doses), although higher doses (4–5 kGy) showed significant reductions (p ≥ 0.05). Color L* values increased at 1–3 kGy (p ≤ 0.05) but declined at 4 and 5 kGy. Textural softening was less pronounced at 8% moisture than 5%, and sensory evaluations indicated that walnuts irradiated at 3 kGy (5%) or 2 kGy (8%) maintained superior acceptability (p ≤ 0.05). These results show gamma irradiation as a strong, non-chemical intervention that simultaneously addresses fungal contamination, aflatoxin load, and lipid stability. Extended shelf life and export-quality parameters of gamma irradiated walnuts can improve India’s competitiveness in the international market, especially in countries that have strict regulatory limits on mycotoxins and quality standards.